2017
DOI: 10.1002/yd.20269
|View full text |Cite
|
Sign up to set email alerts
|

Using Leadership Competencies to Develop Talents into Strengths

Abstract: This chapter describes how to use a leadership competency approach to help students develop their five signature themes from the Clifton StrengthsFinder assessment into strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…While leadership education can be comprised of a variety of approaches, from teaching theories and concepts to extracting leadership lessons from classic literature and philosophers, one approach involves focusing on leadership competency development (Seemiller, 2013a).…”
Section: Leadership Competency Development Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…While leadership education can be comprised of a variety of approaches, from teaching theories and concepts to extracting leadership lessons from classic literature and philosophers, one approach involves focusing on leadership competency development (Seemiller, 2013a).…”
Section: Leadership Competency Development Leadershipmentioning
confidence: 99%
“…Competencies included attention, meaning, trust, and self (Bennis, 1984). In addition, a study by Seemiller (2013a) found that all 97 higher education academic accrediting agencies in the U.S. representing disciplines from education and aviation to engineering to business required students to possess at least one leadership competency by graduation, with the most prevalent being verbal communication. Seemiller (2013a) also found that 30 percent of all academic accrediting organizations included a leadership competency in at least half of their learning outcomes, and in 41 percent of all organizations, the general competency of "leadership" was required.…”
Section: Leadership Competency Development Leadershipmentioning
confidence: 99%
“…Employing a competency-based approach to management enables firms find and develop future leaders (Kim et al, 2020;Mirhosseini et al, 2020). An emphasis on improving management skills and leadership abilities encourages better leadership (Lewis, 2016;Seemiller, 2017). Human resources professionals should take a leader's expertise into account when making selections and planning for their development and contrast it with those who require further development to succeed in a management capacity (Salvage et al, 2019;Wiewiora & Kowalkiewicz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, leadership educators might design programs and course with intentionality (Jenkins & Allen, 2017); this is focusing the internship on developing a specific grouping of leadership competencies. Doing so might allow students to capitalize on their leadership strengths and further enhance the pedagogical value of the internship (Croft & Seemiller, 2017;Seemiller, 2017). leadership as an ongoing learning process (Komives et al, 2005).…”
Section: Methodsmentioning
confidence: 99%